Lymphatic filariasis - Molyneux, CMG, David (Henry Stewart Talks, 2010)
Lymphatic Filariasis as a disabling, mosquito-borne parasitic disease, Control strategies through annual drug therapy, Control of vector mosquitoes, The progress in the Global Programme; mapping, monitoring, evaluation, pathology, morbidity management, Multiple benefits of drugs in other conditions